Non-Cruelty to Animals: A General Principle of (Animal) Law - Sabine Brels (Journal of Animal Law, Ethics and One Health)
In this paper, the author advocates for the recognition of the principle of ‘non-cruelty to animals’ as a General Principle of Law under Article 38(1)(c) of the Statute of the International Court of Justice (ICJ). This principle of ‘non-cruelty to animals’, commonly understood as condemning the unnecessary infliction of suffering on animals, is widely reflected in national legal frameworks, indicating a broad global consensus against cruelty. However, the term ‘unnecessary’ is often applied inconsistently and is open to variable interpretation across jurisdictions. The author therefore proposes interpreting the principle through the lens of avoidability, suggesting a clearer, and in our view more objective standard that suffering should be avoided wherever possible. This reframing would promote a more objective and actionable standard, address subjective exemptions and eliminate activities that cause avoidable suffering to animals, while promoting viable alternatives to animal products and animal-based methods. The author also examines how current anti-cruelty laws are limited, often excluding certain animal groups or exempting practices for traditional, scientific, or economic purposes. By recognizing non-cruelty as a General Principle of Law, the ICJ could officially establish the international value of this principle, ensuring that animal laws consistently reflect a consensual baseline for ethically treating sentient beings. Such recognition would establish non-cruelty as a foundation for new international frameworks, specifically avoiding animal crimes, and would encourage the development of global instruments that universally condemn and prevent animal cruelty. This proposed legal framework would represent a significant advancement in both ethical and legal treatment of animals, affirming a new international commitment to the legal protection of animals as sentient beings.